Familial hematuria: A review - Pavlína Plevová; Josef Gut; Jan Janda (Medicina, 2017)
The most frequent cause of familial glomerular hematuria is thin basement membrane nephropathy (TBMN) caused by germline COL4A3 or COL4A4 gene mutations. Less frequent but important cause with respect to morbidity is Alport syndrome caused by germline COL4A5 gene mutations. The features of Alport syndrome include hematuria, proteinuria and all males with X-linked disease and all individuals with recessive disease will develop end stage renal disease, usually at early youth. In X-linked Alport syndrome, a clear genotype-phenotype correlation is typically observed in men. Deleterious COL4A5 mutations are associated with a more severe renal phenotype and more frequent high-frequency sensorineural hearing loss and ocular abnormalities. Less severe COL4A5 mutations result in a milder phenotype, with less frequent and later onset extrarenal anomalies. The phenotype in females is highly variable, mostly due to inactivation of one of the X chromosomes. Isolated cases may be caused by de novo COL4A5 mutations or by gonosomal mosaicism. Untreated autosomal recessive Alport syndrome, caused by COL4A3 and COL4A4 mutations, is typically associated with ESRD at the age of 23–25 years and extrarenal symptoms in both men and women. The TBMN phenotype is associated with heterozygous carriers of COL4A3, COL4A4 mutations. Molecular genetic testing is the gold standard for diagnosing these diseases. Although genotype-phenotype correlations exist, the phenotype is influenced by modifying factors, which remain mainly undefined. No therapy is available that targets the cause of Alport syndrome; angiotensin-converting enzyme inhibitor therapy delays renal failure and improves lifespan.